Prevalence of polycythaemia with different formulations of testosterone therapy in transmasculine individuals. Issue 6 (21st June 2021) - Nolan, Brendan J.; Leemaqz, Shalem Y.; Ooi, Olivia; Cundill, Pauline; Silberstein, Nicholas; Locke, Peter; Grossmann, Mathis; Zajac, Jeffrey D.; Cheung, Ada S.
Abstract: Background: Masculinising hormone therapy with testosterone is used to align an individual's physical characteristics with his or her gender identity. Testosterone therapy is typically administered via intramuscular or transdermal routes, and polycythaemia is the most common adverse event. Aims: To compare the risk of polycythaemia with different formulations of testosterone therapy in transmasculine individuals. Methods: A retrospective cross‐sectional analysis was undertaken of transmasculine individuals at a primary and secondary care clinic in Melbourne, Australia. A total of 180 individuals who were on testosterone therapy for >6 months was included. Groups included those receiving: (i) intramuscular testosterone undecanoate ( n = 125); (ii) intramuscular testosterone enantate ( n = 31); or (iii) transdermal testosterone ( n = 24). Outcome was prevalence of polycythaemia (defined as haematocrit > 0.5). Results: Mean age was 28.4 (8.8) years, with a median duration of testosterone therapy of 37.7 (24.2) months; 27% were smokers. There was no difference between groups in serum total testosterone concentration measured. While there was no difference between groups in haematocrit, there was a higher proportion of patients with polycythaemia in those who were on intramuscular testosterone enantate (23.3%) than on transdermal testosterone (0%), P = 0.040. There was no statistically significant difference in polycythaemia between intramuscular testosterone undecanoate (15%) and transdermal testosterone, P = 0.066 nor between intramuscular testosterone enantate and undecanoate, P = 0.275. Conclusions: One in four individuals treated with intramuscular testosterone enantate and one in six treated with testosterone undecanoate had polycythaemia. No individual treated with transdermal testosterone had polycythaemia. This highlights the importance of regular monitoring of haematocrit in transmasculine individuals treated with testosterone, and findings may inform treatment choices.